Radiation-induced white matter dysfunction in patients with nasopharyngeal carcinoma - Zheng, Xingyou; Li, Li; Gao, Jian-ming; Hu, Yang; Deng, Limeng; Kang, Ya-fei; Zhang, Youming (Frontiers in Neuroscience, 2025)
Radiation-induced structural abnormalities in white matter (WM) have been reported in patients with nasopharyngeal carcinoma (NPC); however, the alterations in functional domain were insufficiently investigated. A total of 111 NPC patients were included and these patients, based on whether completed radiation therapy (RT) or not, were divided into pre-RT (n = 47) and post-RT (n = 64) groups. Functional connectivity strength (FCS) between WM regions (WW-FCS) and between WM and gray matter (GM) regions (GW-FCS) was used to investigate the radiation-induced changes in WM function. Compared with the pre-RT patients, post-RT NPC patients showed decreased WW-FCS in the left superior cerebellar peduncle, right anterior limb of internal capsule, bilateral posterior thalamic radiation, and left tapetum. Compared with the pre-RT patients, post-RT NPC patients showed decreased GW-FCS in the left caudate, bilateral visual cortex, and the right ventral prefrontal cortex. In the post-RT group, the GW-FCS in left visual cortex was negatively correlated with radiation dosage for the brain stem (r = -0.35, p = 0.039), and for the left temporal lobe (r = -0.46, p = 0.0058). The GW-FCS in right visual cortex was negatively correlated with radiation dosage for the left temporal lobe (r = –0.38, p = 0.025). Our findings of decreased WW-FCS and GW-FCS in such brain regions (such as visual cortex, posterior thalamic radiation, and anterior limb of internal capsule, as well as superior cerebellar peduncle) suggest potential functional impairments in visual and motor systems.